MON-356 Atypical Femur Fracture with Denosumab - Mirza, Faryal S (J Endocr Soc, 2020)
Background: Osteoporosis (OP) is a systemic disease that is associated with increased risk for fractures. Anti-resorptive medications (ARM) are an effective modality for treatment and prevention of fractures in OP. Long-term use of ARM like bisphosphonates (BP) is associated with increased risk of atypical femoral fractures (AFF). Denosumab (DM) is monoclonal antibody that targets receptor activator of nuclear factor KB ligand (RANKL). A few cases of AFF with DM have been reported in patients who have previously been on long term BP therapy. We present a case where the patient had only received two zoledronic acid (ZA) infusions, last one three years prior to being initiated on DM and experienced AFF. Case: 73-year-old postmenopausal woman presented to the emergency room with sudden onset pain in the right thigh. Patient was standing and reaching into her closet when she felt a snap in right thigh followed by inability to move the right leg or bear weight on it. X-ray of the right femur showed a displaced femoral shaft fracture with a short transverse fracture line and a spike, without comminution. History was significant for OP for which she received raloxifene for a couple of years followed by ZA in 2013 and 2015 by her primary care. Fracture history was significant for a wrist fracture in 2015, and T12 and L1 fractures in 2017 from coughing while on Medrol dospak for an acute episode of bronchitis. In 2017, bone density showed L1-L4 T score of -2.0, the left total hip T score was -1.8 and left femoral neck T score was -2.5 consistent with OP. Work up for secondary causes of OP was unremarkable. Due to recent T12 and L1 compression fractures, she was recommended DM. She received DM in June 2018 as she was undergoing a dental implant followed by December 2018 and June 2019 and presented with the right femoral fracture in November 2019. Past history was significant for idiopathic pulmonary fibrosis which had been relatively stable without need for long-term steroid therapy. History was negative for diabetes or kidney disease. Menarche was at age 14, menopause at 52 and she did not take any hormone replacement therapy. She underwent surgical fixation with intramedullary rod. Due to concern about ARM associated sub-trochanteric fracture in the right femur, left femur was imaged. She had cortical beaking in the distal third of the left femur, and underwent prophylactic medullary nailing of the left femur as well. Conclusion: AFF are an uncommon complication of ARM used for OP. Not many cases of AFF have been reported with the use of DM and most of the reported cases are associated with prolonged BP therapy. Our case is unusual in that AFF occurred in the absence of prolonged BP therapy and raises concern that a couple of ZA infusions in the past can also increase the risk of AFF. Clinicians need to have a high index of suspicion and may consider doing femur x-rays in patients who have previously been on BP prior to starting DM.